Chronoamperometry as effective alternative technique for electro‐synthesis of ortho‐phenylendiamine permselective films for biosensor applications. Issue 39 (4th March 2020) - Monti, Patrizia; Bacciu, Andrea; Arrigo, Paola; Marceddu, Salvatore; Migheli, Quirico; Serra, Pier A.; Rocchitta, Gaia
Abstract: Analyte quantification in first generation electrochemical biosensors is threatened by electro‐active molecules, such as ascorbic acid (AA). Electrochemical deposition of ortho ‐phenylendiamine ( o PD) on transducer considerably reduces AA interfering. These properties of poly‐ o PD (PPD) are influenced by electro‐polymerization conditions. Chronoamperometry (CA) is proposed as an alternative technique for o PD electro‐deposition over Pt. Pt/PPD sensors are evaluated through functional parameters related to AA rejection and analytical performances. N2, O2, and air bubbled supporting electrolyte and several step duration times are used. Best performing CA‐PPD sensor is obtained in N2 ‐purged phosphate solution containing 300 mM o PD by means of a 1 s step duration/120 steps CA. High performing PPD is achieved in shorter time compared to commonly used constant potential amperometry. Aging of polymeric features and scanning electron microscopy investigations are performed and optimized CA electro‐polymerization conditions are used to build up an efficient interference blocking layer in a glucose oxidase biosensor. Abstract :